Evaluasi Penerapan Standar Pengelolaan Pendidikan di SMP Negeri 4 Seram Bagian Timur Kecamatan Bula Kabupaten Seram Bagian Timur - Purwosusanto Purwosusanto; Izaak H Wenno (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study aims to evaluate the implementation of educational management standards at SMP Negeri 4 Seram Bagian Timur. The significance of this research is that it is hoped that it can provide useful input for school managers and local governments through the education department, especially in implementing the management of educational standards in schools in accordance with Permendikbudristek number 47 of 2023 with the aim of improving the quality of education. This study uses evaluative research with qualitative methods. This study was conducted at SMP Negeri 4 Seram Bagian Timur. The study subjects were the principal, deputy principal for curriculum, head of student affairs, head of infrastructure, head of public relations, 2 senior teachers who already had teacher certification, and the head of the school committee. Data collection techniques using observation, documentation and interviews. The data analysis technique is carried out in three stages: 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results show that the implementation of education management standards at SMP Negeri 4 Seram Bagian Timur in the context component aspects has been well understood, however the implementation of several aspects in the input and process components has not been implemented well, so the product components have not been implemented well. Theoretical implications can be found that the implementation of education management standards at SMP Negeri 4 Seram Bagian Timur has not been implemented well